Biological control of an agricultural pest protects tropical forests - Wyckhuys, Kris A.G.; Hughes, A.C.; Buamas, C.; Johnson, Anne; Vasseur, Liette; Reymondin, Louis; Deguine, J.P.; Sheil, D. (Springer, 2019)
Though often perceived as an environmentally-risky practice, biological control of invasive species can restore crop yields, ease land pressure and thus contribute to forest conservation. Here, we show how biological control against the mealybug Phenacoccus manihoti (Hemiptera) slows deforestation across Southeast Asia. In Thailand, this newly-arrived mealybug caused an 18% decline in cassava yields over 2009–2010 and an escalation in prices of cassava products. This spurred an expansion of cassava cropping in neighboring countries from 713,000 ha in 2009 to > 1 million ha by 2011: satellite imagery reveals 388%, 330%, 185% and 608% increases in peak deforestation rates in Cambodia, Lao PDR, Myanmar and Vietnam focused in cassava crop expansion areas. Following release of the host-specific parasitoid Anagyrus lopezi (Hymenoptera) in 2010, mealybug outbreaks were reduced, cropping area contracted and deforestation slowed by 31–95% in individual countries. Hence, when judiciously implemented, insect biological control can deliver substantial environmental benefits.